Selected Aspects of Supplementary Pension Savings a Behavioral Perspective - Pieńkowska-Kamieniecka, Sylwia (Studia Oeconomica Posnaniensia, 2017)
The purpose of the paper is to present the basics and behavioral assumptions of the theory of saving and their influence by financial decisions in the area of savings for old age. In addition, using the knowledge of behavioral factors determining saving decisions, helped to identify the possible solutions to help individuals, in the condtions of rationality and limited self-control, making appropriate choices in terms of pension savings. Based on the assumptions of behavioral economics, it can be pointed out that, in contrast to neoclassical economics, people are not rational and all-knowing. Therefore, there is a reasonable apprehension of a lack of, or insufficient, or inadequate action in terms of decision making. These decisions should be therefore supported in such a way, that using appropriate solutions choice architecture makes it easier for them to make appropriate choices. In recent times particularly efective has been implementing auto enrollment in pension programs.